Web-Based Information Technologies and Distributed Systems - Gabillon, Alban; Sheng, Quan Z.; Mansoor, Wathiq; SpringerLink (Online service) (Paris : Atlantis Press, 2010)
The Fourth International Conference on Signal-Image Technology & Internet-Based S- tems (SITIS 2008) has been successfully held during the period 30th November to 3rd of December of the year 2008 in Bali, Indonesia. The Track Web-Based Information Te- nologies & Distributed Systems (WITDS) is one of the four tracks of the conference. The track is devoted to emerging and novel concepts, architectures and methodologies for c- ating an interconnected world in which information can be exchanged easily, tasks can be processed collaboratively, and communities of users with similar interests can be formed while addressing security threats that are present more than ever before. The track has attracted a large number of submissions; only ?fteen papers have been accepted with - ceptance rate 27%. After the successful presentations of the papers during the conference, the track chairs have agreed with Atlantis publisher to publish the extended versions of the papers in a book. Each paper has been extended with a minimum of 30% new materials from its original conference manuscript. This book contains these extendedversions as chaptersafter a second roundof reviews and improvement. The book is an excellent resource of information to researchers and it is based on four themes; the ?rst theme is on advances in ad-hoc and routing protocols, the second theme focuses on the latest techniques and methods on intelligent systems, the third theme is a latest trend in Security and Policies, and the last theme is applications of algorithms design methodologies on web based systems.
A Community-based Approach for Service-based Application Composition in an Ecosystem -- Complexity Analysis of Data Routing Algorithms in Extended Lucas Cube Networks -- An Incremental Algorithm for Clustering Search Results -- Query Planning in DHT Based RDF Stores -- A Formal Methodology to Specify Hierarchical Agent-Based Systems -- Reducing RedundantWeb Crawling Using URL Signatures -- Interoperability Among Heterogeneous Systems in Smart Home Environment -- A Formal Framework to Specify and Deploy Reaction Policies -- A new distributed IDS based on CVSS framework -- Modeling and Testing SecureWeb Applications -- Secure interoperability with O2O contracts -- ADMON: I/O Workload Management by Visage Administration and Monitoring Service -- Extracting Neglected Content from Community-type-content.
Keywords: Computer science; Multimedia information systems; Computer Science; Multimedia Information Systems; Electronic books